HPV18 E1^E4 is assembled into aggresome-like compartment and involved in sequestration of viral oncoproteins. - Kajitani, Naoko; Satsuka, Ayano; Yoshida, Satoshi; Sakai, Hiroyuki (Frontiers in Microbiology, 2013)
Papillomavirus is the etiological agent for warts and several squamous carcinomas. Skin cancer induced by cottontail rabbit papillomavirus (CRPV) was the first animal model for virus-induced carcinogenesis. The target organ of the virus infection is stratified epithelium and virus replication is tightly regulated by the differentiation program of the host cell. E1^E4 protein is a viral gene product, and although it is considered to be involved in the control of virus replication, little is known about the biological role. We found that HPV18 E1^E4 was assembled into an aggresome-like compartment and was involved in sequestration of virus oncoproteins, which might contribute to the differentiation-dependent lifecycle of papillomavirus.